The Role of Complement Cascade in Diabetic Kidney Disease: New Paradigms and Therapeutic Targets - Rico-Fontalvo, Jorge; Aroca-Martinez, Gustavo; Daza-Arnedo, Rodrigo; Rodriguez-Yanez, Tomas; Suarez-Romero, Beatriz; Uparella-Gulfo, Isabella; Bohorquez-Rivero, Jose; Montejo-Hernandez, Juan; Cabrales, Jose; Narvaez-Fontalvo, Carlos (International Journal of Innovative Research in Medical Science, 2022)
Diabetic kidney disease (DKD) is a chronic complication of diabetes mellitus. DKD is a frequent entity, which occurs in approximately 30-40% of diabetic patients. Traditionally, DKD has been considered a non-inflammatory glomerular disease, being perceived as a condition induced primarily by metabolic and hemodynamic changes. Inflammation has been classified as a main phenomenon for the onset and progression of DKD. Today, the inclusion of the inflammatory component is fundamental for the comprehension of the onset and development of this disease. The inflammatory component has multiple pathways, within which the activation and regulation of the complement system is of particular interest. The mechanisms by which complement is part of the multiple inflammatory pathways in DKD are being increasingly understood, which will guide the development of strategies and therapeutic targets.